Evaluation of iron accumulation during childhood cancer treatment - Çalışkan Kamış, Şule; Çil, Metin; Yağcı, Begül; Karagün, Barbaros Şahin (Frontiers in Pediatrics, 2026)
BackgroundIron overload is a major concern in pediatric oncology, especially among patients receiving frequent blood transfusions. Although serum ferritin (SF) is widely used as a surrogate marker, T2* magnetic resonance imaging (MRI) of the liver and heart remains the gold standard for quantifying tissue iron deposition. This study evaluated the relationship between serum ferritin levels and T2* MRI findings in pediatric cancer patients, focusing on those with ferritin levels >1,000 µg/L.MethodsThis retrospective study included patients aged 10–25 years diagnosed with malignancies and followed at the Pediatric Hematology and Oncology Clinic of Adana City Training and Research Hospital between June 2023 and December 2024. The upper age limit was chosen to include adolescent and young adult patients treated under pediatric oncology protocols. Serum ferritin and C-reactive protein (CRP) levels were measured during afebrile, infection-free periods. Elevated ferritin levels concurrent with high CRP were re-evaluated to exclude inflammation-related effects. Transfusion frequency and ferritin levels were recorded at 3, 6, and 12 months. Patients with ferritin >1,000 µg/L underwent cardiac and hepatic T2* MRI to assess organ-level iron burden and determine the need for chelation therapy.ResultsTwenty-eight patients (median age: 14 years; 12 females, 16 males) were analyzed. The median baseline ferritin level was 32.5 µg/L. A significant correlation was found between transfusion number and ferritin >1,000 µg/L within the first 3 months (p = 0.029, r = 0.48) and for total annual transfusions (p = 0.001). Correlations at 3–6 months (p = 0.061, r = 0.42) and 6–12 months (p = 0.065, r = 0.39) were not statistically significant. Three patients (10.7%) had ferritin >1,000 µg/L—two with acute lymphoblastic leukemia and one with non-Hodgkin lymphoma. Among them, one underwent bone marrow transplantation, one died, and one had moderate hepatic but normal cardiac iron on T2* MRI.ConclusionIron overload is a preventable but clinically important complication in pediatric oncology. Combined monitoring with serum ferritin and T2* MRI enables early detection and timely management. Larger multicenter studies are needed to optimize screening intervals and chelation strategies in this high-risk group.